(untitled) (Proceeding of Dakwah Saizu International Conference, 2023)
This research discusses the motivation of someone who wants to stop taking illegal drugs with social rehabilitation, without knowing what rehabilitation is, he seeks out social and internet networks to find out. This study aims to find out how the motivation is formed in a person who uses drugs to be able to stop consuming them. This study uses qualitative methods and a reality counseling approach. Reality counseling is by emphasizing life now to meet the target of achievement you want to aim for. And data collection techniques are carried out by observation and interviews. Drugs are a type of substance that is often used in medicine as a medicinal use. Victims of drug abuse usually consume without being supervised by a doctor because sometimes victims can only consume it to find a soother for various life problems and at first they are just experimenting, but gradually they become addicted and become addicted. Going through the rehabilitation process is not an easy thing but it is very difficult and you have to have encouragement or motivation from yourself to want to stop.